Social Media in Small and Medium-Sized Businesses – Discussion of Potentials and Risks - Nicole WASSENBERG (Communications of International Proceedings, 2021)
Social media has arrived in many small and medium-sized companies. More and more organizations are taking advantage of the benefits and are increasingly using social media. However, activities in SMEs vary greatly and are not yet equally implemented. This situation results from missing know-how about the possibilities of social media on the one hand, but also from the lack of resources on the other hand. The paper at hand outlines how SMEs can make use of social media. It also provides an overview of the potential benefits of social media and illustrates potential risk arising from its usage. The paper concludes with a short outline of the author’s current research activities.
Keywords: Social media; Web 2.0; SME.